Implementasi Teori Kognitif terhadap Kemampuan Literasi Sains Siswa Madrasah Ibtidaiyah - Rina Endang Sulistiowati; I Gede Astawan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Scientific literacy is the ability of students to understand, translate, use information, and evaluate scientific problems in everyday life through critical thinking. This study aims to measure the level of scientific literacy of fifth grade students of MIN 1 Balikpapan, including identifying possible misconceptions. Misconceptions themselves refer to errors in understanding or erroneous concepts held by students. For elementary school teachers, understanding misconceptions is very important because it can be a reflection to improve the quality of science learning in the classroom, which ultimately has an impact on students' scientific literacy abilities. The results showed that the level of scientific literacy of fifth grade students of MIN 1 Balikpapan was relatively high, with 63.3% of students understanding the concept of simple machines well, 13.3% of students not understanding the concept, and 23.3% of students experiencing misconceptions. According to Piaget's theory, improving students' cognitive abilities can be achieved through student-centered learning and encouraging active discovery. However, based on the results of the analysis of scientific literacy questions, three indicators were found that still had low scores (below 60%), namely indicators related to scientific design and science experiments.